ANALISIS PENGARUH PENETRASI MEDAN LISTRIK LINTANG TINGGI KE LINTANG RENDAH TERHADAP IONOSFER SAAT BADAI GEOMAGNET (ANALYSIS OF THE ELECTRIC FIELD PENETRATION EFFECT FROM HIGH TO LOW LATITUDES ON THE IONOSPHERE DURING GEOMAGNETIC STORM) - Anwar Santoso; Dadang Nurmali; Mira Juangsih; Iyus Edi Rusnadi; Sri Ekawati; Anton Winarko; Siska Filawati (Lembaga Penerbangan dan Antariksa Nasional, 2017)
The influence of geomagnetic storms on the ionosphere in the equatorial and low latitudes can be either rising or falling value of the value foF2 with the different response delay time. The difference in response is one of them allegedly influenced by the modification of Equatorial Electrojet (EEJ) generated by the penetration of high latitude electric field towards the low latitude electric field and the equator. Therefore, this paper analyzes the influence of the high latitude penetration of electric current to the low latitude electric current towards the ionosphere response to Indonesia's current geomagnetic storms using the data foF2 BPAA Sumedang (SMD; 6,910 S; 106,830E geographic coordinates or 16,550 S; 179,950 E magnetic coordinates) and data from the Biak geomagnetic field station (BIK; 1,080 S; 136,050 E geographic coordinates or 9,730 S; 207,390 E magnetic coordinates) in 2000-2001. The result showed that the injection of the electric field of the high latitudes to lower latitudes causing foF2 BPAA Sumedang to be disturbed. Onset of the foF2 disturbance in BPAA Sumedang started coincide with EEJ(HBIK-HDRW) and reached its minimum point with a time delay between 0 to 4 hours before and after Dst index reached the minimum point. For a delay time of 0 to 4 hours after the Dst index reached the minimum point, the results were in accordance with the research results from the prior research. However, for the time difference of between 0 to 4 hours before the Dst index reached the minimum point, the results differ from their results. AbstrakPengaruh badai geomagnet terhadap ionosfer di ekuator dan lintang rendah berupa naiknya nilai foF2 atau turunnya nilai foF2 dengan waktu tunda respon berbeda-beda. Perbedaan respon tersebut salah satunya diduga dipengaruhi oleh modifikasi Equatorial electrojet (EEJ) yang dihasilkan oleh penetrasi medan listrik lintang tinggi sampai daerah lintang rendah dan ekuator. Oleh karena itu, dalam makalah ini dilakukan analisis pengaruh penetrasi arus listrik lintang tinggi ke lintang rendah terhadap ionosfer saat badai geomagnet menggunakan data foF2 dari Balai Pengamatan Antariksa dan Atmosfer (BPAA) Sumedang (SMD; 6,910 LS; 106,830 BT koordinat geografis atau 16,550 LS; 179,950 BT koordinat magnet) dan data medan geomagnet dari stasiun Biak (BIK; 1,080 LS; 136,050 BT koordinat geografis atau 9,730 LS; 207,390 BT koordinat magnet) tahun 2000-2001. Hasilnya diperoleh bahwa penetrasi medan listrik dari lintang tinggi ke lintang lebih rendah Indonesia menyebabkan foF2 BPAA Sumedang terganggu. Onset gangguan foF2 BPAA Sumedang mulai terjadi bertepatan dengan EEJ(HBIK-HDRW) mencapai titik minimumnya dengan jeda waktu antara 0 sampai 4 jam sebelum dan sesudah indeks Dst mencapai minimum. Untuk beda waktu 0 sampai 4 jam sesudah indeks Dst mencapai minimum, hasilnya bersesuaian dengan hasil penelitian peneliti sebelumnya. Namun, untuk beda waktu 0 sampai 4 jam sebelum indeks Dst mencapai minimum, hasilnya merupakan temuan berbeda dari hasil mereka.